Knowledge Visualization - Pal, Anup Singh (2003)
Knowledge is universally available and has utility in some context. This makes it very difficult to be copied and duplicated. Organizations in the form of their market insights, strategic information, people, etc. are powerhouse of knowledge. Modern technology has made it possible for them to store and distribute this knowledge easily and efficiently. This has on one hand made huge repositories and data bases available for knowledge storage while on the other hand made it very difficult to comprehend all information and knowledge. Thus concepts like knowledge management have come up. Still they find management of this vastly available resource a big challenge. Knowledge visualization is an answer for the nightmares of these organizations. It not only promises effective representation of this knowledge but also an efficient way to utilize this knowledge for cutting edge over their competitors. In this thesis we have presented an exhaustive overview of knowledge visualization. We have also done a detailed analysis of two application areas of knowledge visualization with real life examples. These two areas of application are websites and e-learning. While for e-learning we have done a detailed study with in-depth data analysis, for websites we have also developed a system apart from study and analysis. For both mentioned areas we have taken example of University of Nottingham in Malaysia (UNiM) and finally generalized the study for any similar systems or examples. Each of these two systems we have studied employs knowledge visualization concepts and comes out with efficient ways in which knowledge visualization can be applied to solve day to day problem of information and data deluge.